Empiric Antibiotics for Serious Bacterial Infection in Young Infants: Opportunities for Stewardship. Issue 8 (August 2015) - Cantey, Joseph B.; Lopez-Medina, Eduardo; Nguyen, Sean; Doern, Christopher; Garcia, Carla
Abstract : Objectives: To evaluate the causative agents of serious bacterial infection (SBI) in young infants and the optimal approach to empiric antibiotic therapy for infants with SBI. Methods: From May 1, 2011, to December 1, 2013, pertinent clinical data were collected on previously well infants 60 days or younger with SBI as defined by a positive bacterial culture from a sterile site. Infants were identified by prospective surveillance of admissions and daily review of microbiology records. Results: Two hundred sixty-five infants with SBI were identified. Mean age was 32 days (SD ±16.6 days). Twenty-nine infants had meningitis, 66 had bacteremia (37 with concomitant urinary tract infection), and 170 had urinary tract infection alone. No methicillin-resistant Staphylococcus aureus, vancomycin-resistant Enterococcus sp., or penicillin-resistant Streptococcus pneumoniae were identified. Four extended-spectrum β-lactamase–producing gram-negative bacilli were seen. Empiric therapy was ampicillin and gentamicin (n = 116, 44%) or third-generation cephalosporin based (n = 149, 56%). Ampicillin and gentamicin, with third-generation cephalosporins reserved for cases where meningitis is suspected, would have provided effective coverage for 98.5% of infants and unnecessarily broad therapy for 4.3%. Third-generation cephalosporins with ampicillin would have been effective for 98.5% of infants and unnecessarily broad for 83.8%. Third-generation cephalosporin monotherapy was less effective than either combination ( P < 0.001). Fifty-seven percent of broad spectrum empiric therapy was continued despite culture results allowing de-escalation. Conclusions: Ampicillin/gentamicin remains an effective empiric regimen for infants 60 days or younger with suspected SBI. Use of a third-generation cephalosporin for suspected meningitis is appropriate, but cerebrospinal fluid must be obtained promptly to guide appropriate therapy.